PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7E DALAM PEMBELAJARAN IPA TERPADU TERHADAP KETERAMPILAN PROSES SAINS SISWA - Nurhaningtyas Agustin (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2018)
This research intent to describe performed learning, skill step-up processes science, and student response by use of learning model 7E in intregated sciences class VIII SMP. This research constitute True Experiment Design. This observational population is all class VIII SMPN 2 Krian Sidoarjo school years 2013 / 2014 ones consisting of 8 classes. Sample that is utilized in this research is class VIII-E as class of experiment and class VIII-F as class of control. Data on observational it is data as yielding as pre-test and post-test skill processes science and studying result, skill observation data processes science and student response questionnaire. Sample gets normal distribution and homogeneous. Result arithmeticing to point out science process skill chastened student with learning model 7E tall increasing happening signifikan's one as big as 0,73 but was reached klasikal's ala thoroughness. Meanwhile studying result happens step-up 0,74 and were reached by presentase thoroughness 97 %. It points out that learning model 7E in integrated sciences theme Biomassa's energy can increase prose's skill science and student studying result. Learning model 7E getting positive response of student.